Analisis Semiotika Lirik Lagu “Angel Baby” Karya Troye Sivan - Irawan, Deddy; Parapat, Dyah Atika; Sazali, Hasan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The song with the title "Angel Baby" is considered to cause debate in the midst of society, especially Indonesian society. Because this song is considered to contain LGBT elements because the singer is Troye Sivan who is allegedly gay. Therefore, the author makes the song to be analyzed. According to the writing, the song is quite interesting to research (analyze). In short, based on the author's observation or analysis, it is concluded that the song Angel Baby is a song that contains LGBT content It is based on the content of the song lyrics and plus the singer who is gay Keywords: Angel Baby, song analysis, LGBT, gay singer